Malinche, Pocahontas, and Sacagawea: Indian Women as Cultural Intermediaries and National Symbols - Khelifa, Amani (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2019)
In her book, Rebecca K. Jager compares and contrasts the lives and legends of three Indigenous North American women: Malinche, Pocahontas, and Sacagawea. Jager’s research answers an earlier call by Native-American historian and feminist scholar Clara Sue Kidwell in her 1992 Ethnohistory article, “Indian Women as Cultural Intermediaries,” to revisit these stories from a non-Eurocentric perspective.